Application of Zinc and Iron-Based Fertilizers Improves the Growth Attributes, Productivity, and Grain Quality of Two Wheat (Triticum aestivum) Cultivars - Hafeez, Muhammad Bilal; Ramzan, Yasir; Khan, Shahbaz; Ibrar, Danish; Bashir, Saqib; Zahra, Noreen; Rashid, Nabila; Nadeem, Majid; Rahman, Saleem ur; Shair, Hira; Ahmad, Javed; Hussain, Makhdoom; et al. (Frontiers in Nutrition, 2021)
Field-based experiments were conducted during wheat cultivation seasons of 2017-2018 and 2018-2019 to minimize the impact of hidden hunger (micronutrient deficiencies) through agronomic biofortification of two wheat cultivars with zinc and iron. Two spring-planted bread wheat cultivars; Zincol-16 (Zn-efficient) and Anaj-17 (Zn-inefficient with high yield potential) were treated with either zinc (10 kg/ha), iron (12 kg/ha) or their combination to study their effect on some growth attributes (plant height, tillers and spike length etc.), productivity and quality. No application of zinc and, iron or their combinations served as the control. Maximum Zn and Fe contents of grains were improved by sole application of Zn and Fe, respectively. Higher concentration of Ca in grains was observed by combined application of Zn and Fe. Starch contents were found maximum by sole application of Fe. Sole or combined application of Zn and Fe reduced wet gluten contents. Maximum proteins were recorded in Anaj-17 under control treatments. Zincol-16 produced maximum ionic concentration, starch contents, and wet gluten as compared to Anaj-17. Yield and growth attributes were also significantly (P < 0.05) improved by combined application as compared to the sole application of Zn or Fe. The combined application also produced the highest biological and grain yield with a maximum harvest index. Cultivar Anaj-17 was found more responsive regarding growth and yield attributes comparatively. The findings of the present study showed that combined application of Zn and Fe produced good quality grains (more Zn, Fe, Ca, starch and less gluten concentrations) with a maximum productivity of bread wheat cultivars.